Green transformational leadership and financial performance in micro and small enterprises: the interplay of circular economy practices and environmental uncertainty - Oktrivina, Amelia; Sumail, La Ode; Hendryadi, Hendryadi; Effendi, Syahrul; Budiantoro, Harry; Astuti, Shinta Budi (Frontiers in Sustainability, 2025)
Circular economy (CE) practices have become a central issue in management and entrepreneurship research, particularly in emerging economies where micro and small enterprises (MSEs) dominate the business landscape. This study explores how green transformational leadership impacts financial performance through the mediation of corporate entrepreneurship practices, while also examining the moderating role of environmental uncertainty. Data was collected using a two-phase, time-lagged survey design involving 353 Indonesian MSEs. Partial least squares structural equation modeling (PLS-SEM) was employed to test the model. The analysis reveals that GTL has a significant positive effect on CE practices (β = 0.37, p < 0.01) and CE practices strongly enhance financial performance (β = 0.44, p < 0.01). The findings also confirm that CE practices mediate the relationship between green transformational leadership and financial performance (β = 0.16, p < 0.01). Moreover, environmental uncertainty was found to significantly weaken the positive relationship between GTL and CE practices (β = −0.21, p < 0.01). However, it did not have a significant moderating effect on the CE practices-financial performance relationship. This study offers valuable insights for MSE owners and policymakers in emerging Asian economies on leveraging leadership strategies to balance sustainability and financial goals.